2011
DOI: 10.1016/j.pscychresns.2011.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Structural evidence for involvement of a left amygdala-orbitofrontal network in subclinical anxiety

Abstract: Functional neuroimaging implicates hyperactivity of amygdala-orbitofrontal circuitry as a common neurobiological mechanism underlying the development of anxiety. Less is known about anxiety-related structural differences in this network. In this study, a sample of healthy adults with no history of anxiety disorders completed a 3T MRI scan and self-report mood inventories. Post-processing quantitative MRI image analysis included segmentation and volume estimation of subcortical structures, which were regressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
56
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 96 publications
9
56
0
1
Order By: Relevance
“…In RPD, by contrast, anxiety but not apathy significantly correlated with performance on verbally mediated tasks. This finding provides additional support to lesion studies and neuroimaging reports relating anxiety to left-hemisphere dysfunction [59–61, 63, 65]. Taken together, our results demonstrated a differential association of apathy and anxiety with cognition in PD.…”
Section: Discussionsupporting
confidence: 89%
“…In RPD, by contrast, anxiety but not apathy significantly correlated with performance on verbally mediated tasks. This finding provides additional support to lesion studies and neuroimaging reports relating anxiety to left-hemisphere dysfunction [59–61, 63, 65]. Taken together, our results demonstrated a differential association of apathy and anxiety with cognition in PD.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are in line with other populations, where left amygdala volumes have been negatively correlated with both state and trait anxiety levels in normal population and with anxiety state in panic disorder [46, 47]. In fact, in emotion studies, a lateralization to the left in amygdala activation has been reported, particularly for negative emotions, which may play a role in our results [48].…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with a previous report that an intravenous injection of alcohol decreases limbic brain response to fearful faces in healthy individuals (Gilman et al, 2008). Given the critical role of the amygdala and OFC in modulation of anxiety and aversive emotion (Blackmon et al, 2011;Grachev & Apkarian, 2000;Urry et al, 2006), these results support the well-known effects of alcohol in its ability to reduce anxious and negative emotion via reduction in amygdala activity or amygdala-OFC connectivity in response to aversive emotions in healthy individuals.…”
Section: Acute Effects Of Alcohol On the Prefrontal-limbic-striatal Csupporting
confidence: 92%